Impact of harvest by humans on mussel populations around Easter - Ferreira, Ana (2014)
The current macroeconomic scenario has subjected Portuguese coastal areas to greater human pressure caused by the ever-increasing shellfish harvest. Every year on Holy Friday, hundreds of people make their way to coastal areas and frantically capture hundreds of bags worth of mussels in a short amount of time. It causes not just inevitable and profound changes to the intertidal zone, but also slows down its recovery. In 2010 Cascais Municipality (CM) was made aware of this problem and in 2011 and 2012 released a general awareness campaign entitled “In Easter who pays is the mussel”. More than just providing a legal perspective, the goal was to test the impact of said campaign in Meixilhoeiro’s mussel beds. Biological data sampling in “Mexilhoeiro” was conducted over a three-year period, from 2010 to 2012. In 2010 there was no awareness campaign but sampling was done after Holy Friday. In 2011 and 2012 it was done both after and before Holy Friday. The average length and coverage percentage of individuals in rocks were recorded. The subsequent graphical analysis indicated that the average coverage percentage of mussels had been decreasing over the years. However a positive sign was recorded in after the 2012 awareness campaign, when the average length of individuals showed an increase. This could mean a reduction in harvesting during Holy Friday. Results suggest that awareness campaigns are effective measures in the immediate protection of marine resources, when supported by reinforcement in surveillance from fisheries protection authorities. For such improvements to persist, so must those efforts. Beachgoers in the summertime can have a detrimental impact on mussel bed size. Prohibiting recreational fishing will not suffice.